THE POWER OF TRUTH OF PARRHESIA AND PARRHESIASIST IN THE POETRY COLLECTION OF ARAKIAN BALLAD - Maria Matildis Banda (Sanata Dharma University, 2019)
According to power of their truth, poets have a responsibility in expressing the truth through their works. Therefore, the personal relationship between poets and their works is an absolute thing that can be examined from both personal and cultural point of view. This paper analyzes it through the poetry collection of Ballada Arakian (Arakian Ballad) (2014) written by Yoseph Yapi Taum (Yapi) with the main issue of how are the actual forms of personal relationship between Yapi and Arakian Ballad? This paper was written by using expressive approach to answer the issue. The theory used was the theory of power and truth by emphasizing parrhesia (fearless speech) and parrhesiasist (the one who uses parrhesia) according to M. Foucault. The method used was literature review and written interview to the poet. The result shows that the power and the truth owned by Yapi in the parrhesia implementation in his poetry collection, Arakian Ballad, express general themes about humanisms, religious, and reflection based on parrhesia: the poets personal relationship and the truth, the risk he faced in conveying the truth, and the poets responsibility as the parrhesiasist.